Acceptability of doctor-to-nurse task shifting for the integrated management of hypertension and diabetes mellitus in primary care in Benguet, Philippines - Tamayo, Reiner Lorenzo Jarabe; Moncatar, TJ Robinson T. (Manila College of Public Health, University of the Philippines Manila, 2023)
Background. Doctors-to-nurse task shifting, the delegation of specific healthcare tasks from physicians to nurses , has gained attention as a potential strategy to address workforce shortages, improve access to care and optimize healthcare delivery. In the Philippines, where access to medicines and health services remains a public health challenge due to shortages of doctors, task shifting is yet to be examines as an acceptable human resource management strategy in the management of diabetes and hypertension in primary care.

Objectives. The objectives of the study is threefold: (a) describe doctor-to-nurse task shifting in the integrated management of hypertension and diabetes mellitus in primary care in Benguet province, (b) explore the perceptions on doctor-to-nurse task shifting for the management of hypertension and diabetes mellitus in primary care among key stakeholders in Benguet province; and (c) identify priority areas for the harmonization of nursing and medical professions' scopes of practice in the context of integrated management of hypertension and diabetes mellitus in primary care in Benguet.

Methods. This study utilized a convergent parallel mixed methods design. Data was primarily collected through a combination survey, key informant interviews, and focus group discussions using semi-structured questionnaires. The Theoretical Framework of Acceptability developed by Sekhon et al. (2017) was used to explore the acceptability of doctors-to-nurse task shifting among stakeholders using the seven component constructs of acceptability on a concurrent basis.

Results. We found that participants generally has positive views on task shifting, although there were concerns about the long-term shortage of physicians. The study highlighted the importance of a regulatory framework, certification, training, and infrastructure to support task shifting. Additionally, it emphasized the need to review professional laws and scopes of practice and identified areas where collaboration and harmonization between doctors and nurses could be beneficial. To ensure that health professionals have the required skills to carry out shared tasks, pre-service courses may need to be revised. Monitoring and evaluation can assist in ensuring that task sharing is performed properly to provide satisfactory outcomes. The Theoretical Framework of Acceptability provided a good framework for the analysis which provided a new lens to understand key determinants of acceptability. But the importance of implementation strategies could have been missed without doing additional inductive coding.

Conclusion and recommendations. This study found that in Benguet, Philippines, stakeholders had a positive view regarding task shifting from doctors to nurses as a means to enhance health equity. Our findings shed light into what aspects of task shifting were perceived as important in relation to acceptability and suggest ways on how to increase support for it. While its benefits are evident, its implementation requires careful planning and coordination. Policy and decision-makers should take context-specific aspects into account and solve potential problems to ensure the successful integration of task shifting into the health system.
Includes references.
Thesis
Keywords: Task analysis in health care -- Philippines -- Benguet; Hypertension -- Treatment -- Philippines -- Benguet; Diabetes -- Treatment -- Philippines -- Benguet; Physician and nurse -- Philippines -- Benguet